The Isaac Newton Telescope Monitoring project: Stellar population in the IC 10 dwarf irregular galaxy - Mahtab Gholami; Mohammad Taghi Mirtorabi (Iranian Journal of Astronomy and Astrophysics)
We have conducted an optical monitoring survey of IC 10 dwarf irregular galaxy in the Local Group, using the Isaac Newton Telescope (INT) with the wide-field camera (WFC), to identify the Asymptotic Giant Branch stars (AGBs). AGBs are at the final stage of their evolution and can be implemented as powerful tools for finding the star formation history and chemical evolution of galaxies. The stellar populations in IC 10 had not been previously identified in optical wavebands surveys. Our data set was obtained in the i- and V-band with the WFC instrument. Photometry was obtained for 48578 stars within the area of 0.07 deg^2 (13.5 kpc^2), of which 10800 stars are detected as AGBs. Radial distribution histogram has been constructed in the image plane for populations of AGBs, RGBs (Red Giant Branch stars) and massive stars. We found that the RGBs population has the largest effective radius among the three populations in the IC 10 image plane. Our data were matched to optical catalogues of Pan-STARRS (The Pan-STARRS release 1 (PS1) survey-DR1) catalogue, mid-infrared catalogue of good sources (DUSTiNGS Good Source Catalog (GSC)) from the Spitzer Space Telescope and near-IR catalogue of Hubble Space Telescope (HST). The number of 441 and 1927 were identified as C-type (carbon-rich) and M-type (oxygen-rich) stars respectively; using the matched stars between our catalogue and the HST catalogue.